Middle Eocene Paleoenvironmental Reconstruction in the Gonjo Basin, Eastern Tibetan Plateau: Evidence From Palynological and Evaporite Records - Wang, Licheng; Yuan, Qin; Shen, Lijian; Ding, Lin (Frontiers in Earth Science, 2022)
The early uplift of the Tibetan Plateau (TP) had a tremendous influence on the paleoenvironment and paleoclimate. However, we still have little information about the link between the paleoclimatic changes and flora ecosystem caused by the uplift. The Eocene fluvial-lacustrine sequences in the Gonjo Basin, eastern TP, provide excellent archives of the paleoecological and paleoclimatic responses to the surface uplift of the TP. In this study, we investigated a section of the Middle Eocene Ranmugou Formation and used the spore-pollen assemblages, sedimentology, and geochemistry of the evaporites to reconstruct the paleoclimate and paleovegetation. The palynological assemblages reveal that the Middle Eocene ecosystem in the Gonjo Basin was dominated by temperate deciduous broad-leaved forests. The 87Sr/86Sr ratios (0.709942 to 0.710062) of all of the gypsum samples are higher than those of contemporaneous seawater, while the δ34S values (10.3 to 11.0‰) are much lower, indicating an arid lacustrine environment. Combined with published palynological and paleoelevation data for eastern Tibetan lacustrine basins, we infer that the paleoenvironment changed from a warm desert in the Early Eocene to cool and arid deciduous broad-leaved forests in the Middle Eocene, and to arid steppe-desert vegetation in the Late Eocene. The changes in the paleoclimate and vegetation were primarily driven by the surface uplift of the Central Watershed Mountain, the high topography of which blocked the moisture from the Asian Eocene monsoon.